Catching-up and regional disparities: a resource-allocation approach. Issue 1 (2nd January 2021) - Capello, Roberta; Cerisola, Silvia
ABSTRACT: While the allocation of regional assets has been theoretically and empirically analysed in regional growth theories, the subsequent logical step on how such allocation affects regional inequalities has not found direct quantitative validation. This paper tries to fill this gap by presenting an original simulation able to capture the relative weight of each economic resource in the process of decreasing regional disparities. Results witness that not all resources play the same role and that inequalities are better overcome when growth assets fit the regional productive specialization. The former result represents a guide for raising policymakers' awareness on resource priority investments, while the latter proves once again that the local productive vocation is dramatically relevant, and that Cohesion Policy cannot be designed without considering local specificities, in line with the theoretical arguments of the Smart Specialization Strategy.